Agronomic characterization of forage grain crops - Silva, Eranildo Brasil da; Carneiro, Maria Socorro de Souza; Santiago, Flávia Louzeiro de Aguiar; Edvan, Ricardo Loiola; Bezerra, Leilson Rocha; Pereira, Elzânia Sales (Comunicata Scientiae, 2016)
The aim of this research was to accomplish agronomic and chemical composition of four forage species under the Brazilian semiarid conditions . The experimental design was a randomized block, in which the treatments consisted of forage crops: corn cv. BRS 205, millet cv. BRS 1501, sorghum cv. IPA 467-4-2 and sunflower cv. Catissol 01, with four repetitions. It was measured plant height (m2), number of plants, leaf/stem ratio, dry matter percentage, total dry matter and the chemical composition of different forage species. The sorghum showed a greater growth, reaching a height of 270.90 cm. For the leaf/stem ratio, the best results were observed by corn, followed by sunflower. In the chemical composition, the sunflower stood out compared to the other materials for crude protein, lipids and mineral contents. Sorghum present greater growth and mass production of straw for the Brazilian semi-arid conditions. The studied species have appropriate chemical composition characteristics, except for sunflower that has high ether extract contents.